Correlation Between Tissue Densities in Computed Tomography and Three Different Cone-Beam Computed Tomography Units (In Vitro) - S Mehralizadeh; AR Talaipour; P Olyaee; M Amiri siavoshani (Islamic Azad University, 2020)
Background and Aim: Bone density is of great assistance in the selection of the proper implant site. The present study aimed to assess the correlation between tissue densities in computed tomography (CT) and three different cone-beam computed tomography (CBCT) units. Materials and Methods: In this descriptive study, a radiographic phantom consisting of a transparent polymethyl methacrylate (PMMA) cylinder with a 50-mm height and a 50-mm diameter was used, which comprised eight materials, including air, fat, water, PMMA, muscle, cortical bone, cancellous bone, and aluminum. Each material was of 5 mm height and 5 mm in diameter. A 20-mm-thick hollow plexiglass cylinder was used to simulate the soft tissue. The phantom was scanned four times using 16-Slice Lightspeed CT, NewTom VGi, CRANEX 3D, and Rotograph Evo 3D CBCT units. The data were primarily reconstructed and transferred to the OnDemand 3D software in the Digital Imaging and Communications in Medicine (DICOM) format. All the assessments were made in the sagittal plane, and the average density of each of the mentioned eight materials was calculated with the proper grayscale value calculation of each system, which utilizes a simulation inherent density calculation for any region of interest (ROI). Results: The results showed that tissue densities are different in CT and CBCT units. The values estimated by the CRANEX 3D unit approximated that of CT, followed by NewTom VGi and Rotograph Evo 3D CBCT units. Kruskal-Wallis test showed that the differences in the scores are statistically significant (P<0.01), Conclusion: Considering the results, CBCT cannot accurately calculate tissue density.